Constructing a global theology: An assessment of the Christian dogmatics of Veli‐Matti Kärkkäinen. Issue 4 (5th December 2018) - Urvas, Sanna; Vainio, Olli‐Pekka
Abstract: This article examines the recent multivolume Christian Dogmatics, by Veli‐Matti Kärkkäinen. The authors offer an overview to the postfoundationalist methodology of the work and assess how Kärkkäinen succeeds in his dialogue with the sciences and other religious traditions.